Nasilje v športu med mladimi športniki - Strašek, Nika (Mednarodno inovativno poslovanje, 2023)
Violence, as an inappropriate form of behavior, is increasingly appearing in sports as well. The growing occurrence of violence in sports is a consequence of current socio-economic conditions and, above all, the glorification of the importance of winning, which is becoming more important than the original meaning of sports. With the development of sports and its branches, as well as changes in its significance in society, new forms of violence in sports have emerged. Violence is increasingly present even in sports disciplines where it was previously unknown. Awareness of the existence of violence in sports, and especially its recognition, are key elements in the process of its prevention. In this article, through the results of our own research conducted by personally surveying young athletes from various sports disciplines competing in both Slovenian and international competitions, and through numerous international examples, we have highlighted some of its negative effects, both on individuals and on society as a whole. If this article contributes even a fraction to raising awareness about the problem of violence and violence in sports, and its prevention, then we have achieved its purpose.
Keywords: examples of violence; nasilje; Nasilje v športu; primeri nasilja; sports; šport; Športniki; types of violence; violence; vrste nasilja